2006
DOI: 10.1051/alr:2007005
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of small fishes in a shallow macrophytic lake (Niushan Lake) along the middle reach of the Yangtze River, China

Abstract: -This study describes the current status of the small fish community in Niushan Lake in China, and examines the spatial and seasonal variations of the community in relation to key environmental factors. Based on macrophyte cover conditions, the lake was divided into three major habitat types: (1) Potamogeton maackianus habitat, (2) Potamogeton maackianus and Myriophyllum spicatum habitat, and (3) uncovered or less-covered habitat. Fish were sampled quantitatively in the three habitat types by block nets season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 28 publications
2
41
1
Order By: Relevance
“…Pseudorasbora parva is a small planktivore and feeds mainly on aquatic insects, algae, and zooplankton Xie et al, 2000;Yang et al, 2004). This fish species is extremely abundant and plays an important role in fish communities in shallow lakes along the middle reach of the Yangtze River , Xie et al, 2001Xie et al, 2005;Ye et al, 2006). However, we found no study documenting the effects of P. parva on eutrophication in shallow lakes.…”
Section: Introductionmentioning
confidence: 65%
“…Pseudorasbora parva is a small planktivore and feeds mainly on aquatic insects, algae, and zooplankton Xie et al, 2000;Yang et al, 2004). This fish species is extremely abundant and plays an important role in fish communities in shallow lakes along the middle reach of the Yangtze River , Xie et al, 2001Xie et al, 2005;Ye et al, 2006). However, we found no study documenting the effects of P. parva on eutrophication in shallow lakes.…”
Section: Introductionmentioning
confidence: 65%
“…A lot of empirical studies undertaken in temperate and subtropical lakes have shown that macrophytes offer fish increased foraging opportunities, reduced predation risk, and suitable spawning sites (Dibble et al 1996). Our previous studies in the shallows Yangtze lakes found that the spatial distributions of many fishes are positively associated with submerged macrophytes due to the benefits provided by macrophyte cover (Ye et al 2006). Our research in Lake Erhai, the second largest lake in the Yunnan Plateau, also indicated that the majority of fish species in the lake preferred habitats with abundant macrophytes (Tang et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…only listed as introduced fish species without any abundance description by Yang (1996)], and thus assessments of their ecological impacts on local fish community and ecosystem function are unavailable so far. This situation existed partly because these noncommercial species are not targeted by the artisan fisheries of Lake Dianchi and fishery-dependent sampling on the scale that is needed to truly understand fish distribution is costly and usually was given low priority Biol Fish (2015) 98:209-224in lake management (Ye et al 2006). In this light, our experimental sampling with the multiple mesh-sized gillnets can provide an alternative method to evaluate population status of these non-commercial small fish species as well as monitor their long-term dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, depended on varied study scales, completely different driving factors were emphasized. For instance in local studies, surface area, water depth, water quality (dissolved oxygen, total phosphorus, total nitrogen, chlorophyll a, transparency), habitat type and relative organisms (fish, zooplankton, phytoplankton and macrophtye) were sometimes over-emphasized as potential factors linked to fish species richness and assemblages (Mehner et al, 2005;Ye et al, 2006;Cheng et al, 2012). But climatic factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several decades, on-going efforts have been studying fish and fisheries in Chinese lakes. Most studies focused on fish biology, fish community and fish stock enhancement in single or a few lakes in local area (Xie et al, 2001;Ye et al, 2006;Cheng et al, 2010). However, due to the difficulties in compiling reliable and large database of fish species in Chinese lakes, there has been surprisingly little effort to investigate lake fish assemblages related to multiple environmental factors in large spatial scale up until now .…”
Section: Introductionmentioning
confidence: 99%